SYDE1 Acts as an Oncogene in Glioma and has Diagnostic and Prognostic Values - Han, Zhenyuan; Zhuang, Xiaodong; Yang, Biao; Jin, Lihui; Hong, Pengjie; Xue, Junqing; Chen, Shunjie; Tian, Zhen (Frontiers in Molecular Biosciences, 2021)
Objectives: Gliomas remain a serious public health problem worldwide and demand further and deeper investigation. The aim of this study was to explore the association between synapse defective protein 1 homolog 1 (SYDE1) and gliomas via public database excavation and in vitro validation to determine potential diagnostic and prognostic values. Methods and Results: Compared to that in healthy brain tissues, there was a significant increase in SYDE1 expression in glioma tissues. Additionally, SYDE1 exhibited higher expression levels in glioma patients with unfavorable clinicopathological factors. In vitro knockdown of SYDE1 in glioma cell lines A172 inhibited the migrative and invasive abilities but not the proliferative abilities. GO and KEGG analyses of the top 100 genes coexpressed with SYDE1 showed enrichments of tumor-associated terms. Further bioinformatic analysis identified that the SNHG16/hsa-miR-520e/SYDE1 axis might be involved in glioma development. Conclusions: SYDE1 is expressed at higher levels in gliomas than in healthy brains, and can promote metastasis and invasion but not proliferation of gliomas. Thus, SYDE1 has values in the diagnosis and prognosis prediction of gliomas.